Emotional Intelligence at Workplace: A Study of Selected Professionals in India - Bala, Kiran; Chawla , Arvinder Singh (Gyan Management Journal, 2012)
The purpose of current research is to examine the level of Emotional Intelligence among a sample of Indian professionals. Emotional Intelligence has gained significant ground over the last two decades. There have, however, been relatively few empirical studies on El conducted in India, and so little is known of how emotionally intelligent Indian professionals are. Also, much of the research relating to emotional intelligence, has centered on various theories with very little emphasis on individuals within a workplace context.This study aims to throw some light on emotional intelligence le’.lels of Indian professionals. On the basis of the findings, tentative suggestions are provided for enhancing the future El research..